Large‐Area Synthesis of Ultrathin, Flexible, and Transparent Conductive Metal–Organic Framework Thin Films via a Microfluidic‐Based Solution Shearing Process (Adv. Mater. 12/2022). Issue 12 (24th March 2022) - Lee, Taehoon; Kim, Jin‐Oh; Park, Chungseong; Kim, Hanul; Kim, Min; Park, Hyunmin; Kim, Ikjin; Ko, Jaehyun; Pak, Kyusoon; Choi, Siyoung Q.; Kim, Il‐Doo; Park, Steve
Abstract : Gas Sensors In article number 2107696, Il‐Doo Kim, Steve Park, and co‐workers introduce a microfluidic‐based solution shearing combined with post‐synthetic rapid crystallization (MASS‐PRC) process, which enables the formation of high‐quality conductive, flexible and transparent Ni3 (HITP)2 films with thickness controllability down to 10 nm in a rapid large‐area scalable manner. They fabricate hydrogen sulfide (H2 S) gas sensors using the film, which can detect the target gas under humid conditions, and exhibit the highest sensing performance to date.